Geopolitical chessboard: China’s Belt and Road Initiative and shifting power dynamics - Iffat Ara Jasmin; Imran Hosen; Ananda Kumar Biswas (Discover Global Society)
Abstract The Belt and Road Initiative (BRI), inaugurated by Chinese President Xi Jinping in 2013, aims to revive China’s global standing through massive infrastructure, transportation, energy, and trade links across Asia, Africa, and Europe through both land and waterways unveiling the ancient Silk Road legacy. BRI as an economic inducement creates economic dependency and alternative financial systems for nations that challenge the traditional USA-based ‘Bretton Woods System’, further paving the way for creating a “China-centric world order”. Through BRI, China posits itself as one of the critical players in these global fora that emerges a new era of geoeconomics under Chinese leadership through which China is leveraging its political gains. The paper considers the perspectives of economic diplomacy and how BRI acts as an economic tool that further enhances China’s political motives through analyzing some case studies from Asia, Middle East, Africa and Europe. Further, the study analyzes the impacts of BRI through the lenses of realism and constructivism to understand the practical implications of the theory and comprehend the shifting nature of global power dynamics. Employing qualitative methods, the study analyzes the question: To what extent does China's Belt and Road Initiative maximize China’s hegemony in global power dynamics? The study finds that BRI has enormous scope to make China a revisionist state challenging the USA and Western hegemonic power through redefining global power relations in the twenty-first century. Additionally, the article further contributes to the contemporary discussion on multipolarity in the political, social, and economic spheres. The study is significant to the Sustainable Development Goals (SDGs) as it contributes to SDG 9 (Industry, Innovation, and Infrastructure) and SDG 17 (Partnerships for the Goals) through infrastructure investments and international cooperation.